The Impact of Modern Technological Management Strategy on the Quality of Scientific Research in Some Faculties of Physical Education and Sports Sciences in Libyan Universities - Al-Kilanii, Abdul Bari; Boukari, Samia; Turki, Olfa; Attia, Ahmed; Hamouda, Ashraf; Gaied Chortane, Sabri; Alyasir, Saleh; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2024)
This research aims to clarify the role of technological management strategy by identifying the quality of scientific research in the faculties of physical education and sports sciences in Libyan universities. In addition, this study aims to study the role of human resources management in the transition to bringing about the modern technological change in management strategy. Concentrating the process of bringing and attracting modern technology has become an inevitable necessity on the one hand, and a planned and non-random matter on the other hand. In this research, we relied on the descriptive method using the survey method. The study sample was composed of professors from some faculties of physical education and sports sciences of the Libyan University. The total sample number was ninety-one (91) individuals. Several statistical tools were used in this study using SPSS, version 2020, This research resulted in that the strategy of modern technological management has a role in achieving change in universities colleges during their management of various educational programs, especially when it concerns a radical change in the methods of administrative work. Therefore, adopting the digital style by introducing modern technology in the management of local administration is inevitable and imposed by the rapid developments in various means of communication and modern technologies.